MANAJEMEN LABA, MEKANISME CORPORATE GOVERNANCE DAN PENGHINDARAN PAJAK - Setiorini, Hesti; Indriani, Rini; Midiastuty, Pratana Puspa (UNIB Press, 2017)
This study aims to examine the effect of earnings management and corporate governance mechanisms on tax avoidance.The population in this study were property and real estate companies listed on the Indonesia Stock Exchange in 2013-2016. The sampling technique in this study using the purposive sampling technique, with 128 data selected as samples. The analytical method used is multiple linear regression with the SPSS program.The regression analysis results prove that earnings management has an effect on tax avoidance. This study cannot prove the effect of the proportion of independent commissioners, audit committee and managerial ownership on tax avoidance.